A Hybrid Antiperovskite with Strong Linear and Second‐Order Nonlinear Optical Responses. Issue 42 (12th September 2022) - Li, Minjuan; Zhang, Xu; Xiong, Zheyao; Li, Yanqiang; Zhou, Yang; Chen, Xin; Song, Yipeng; Hong, Maochun; Luo, Junhua; Zhao, Sangen
Abstract: Antiperovskites have been studied since the 1980s because of their rich physical and chemical properties, but their linear and second‐order nonlinear optical responses remain largely unknown. Here we report a new polar crystal, Cs3 Cl(HC3 N3 S3 ) (I ), which features a quasi‐one‐dimensional antiperovskite structure composed of ClCs6 polyhedra and A‐site [HC3 N3 S3 ] 2− rings. To our best knowledge, this kind of antiperovskite structure is reported for the first time. Remarkably, I exhibits a very strong nonlinear optical response up to 11.4 times that of the benchmark KH2 PO4 and exceptionally large birefringence of 0.52. The first‐principles calculations and structural analyses reveal that [HC3 N3 S3 ] 2− is the "material gene" while the antiperovskite structural feature making it in a favorable arrangement. This work provides a new structural platform for the rational design of integrated optoelectronic materials with linear and second‐order nonlinear optical responses. Abstract : Hybrid halide antiperovskite Cs3 Cl(HC3 N3 S3 ) could not only double the frequency of incident ray with very strong SHG response but also divide an incident ray into polarized o ray and e ray with exceptionally large birefringence.